Theoretical features of the creative society - Reimeris, Ramojus (Creativity Studies, 2016)
The purpose of this article is twofold. Firstly to analyse and to describe the phenomenon of creative society and to propose the features, distinguishing it from the predecessors – information society and knowledge society. Secondly to reveal the relation of creative society with creative economy and regional specialization. Research is based on the analysis of the relevant literature. The findings reveal that creative society is an extension to information society and knowledge society, but with the different set of main features. Creative society is foundation of the creative economy embedded to the place where it exists. It is organized in non-hierarchical form and opts for the exclusivity, with individual approach to the creation and specific roots in the education. By its nature the creative society is very place-specific and specialized by education and enabled by technology, constantly exploiting its specialization for the innovation activities and economic benefits. This research paper might be a valuable source of information for studying the development of creativity, society in general and creative economy. The further research and practical application could be used to develop indictors of creative society and apply them to study different regions with different specializations. First published online: 14 Sep 2015